2017
DOI: 10.1080/00016489.2017.1416168
|View full text |Cite
|
Sign up to set email alerts
|

Low 25-hydroxyvitamin D levels in postmenopausal female patients with benign paroxysmal positional vertigo

Abstract: Our study suggests that low 25 (OH) D may be a risk factor for BPPV in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 18 publications
2
27
0
Order By: Relevance
“…59,60 The vitamin D level is particularly low in postmenopausal women with BPPV. 61 A low vitamin D level is associated with osteoporosis, and medication to treat osteoporosis can provide protection against BPPV and reduce the incidence of recurrence. 62,63 Talaat et al 64 reported that the rate of recurrence of BPPV in patients with an elevated serum vitamin D level following replacement therapy was quite low during the follow-up period (4%) when compared with that in patients with a low serum vitamin D level (43%).…”
Section: Osteoporosis and Vitamin D Insufficiencymentioning
confidence: 99%
“…59,60 The vitamin D level is particularly low in postmenopausal women with BPPV. 61 A low vitamin D level is associated with osteoporosis, and medication to treat osteoporosis can provide protection against BPPV and reduce the incidence of recurrence. 62,63 Talaat et al 64 reported that the rate of recurrence of BPPV in patients with an elevated serum vitamin D level following replacement therapy was quite low during the follow-up period (4%) when compared with that in patients with a low serum vitamin D level (43%).…”
Section: Osteoporosis and Vitamin D Insufficiencymentioning
confidence: 99%
“…Lack of muscle mass and muscle strength occurs as important organic changes by aging and is remarkably associated with an elevated risk of falls and subsequent osteoporotic fractures, besides this severely influences the potential of movement (Orsatti et al, 2011[26]; Muir and Montero-Odasso, 2011[25]). Vitamin D deficiency is common among older populations worldwide, as more than 60 % of postmenopausal women are vitamin D deficient, regardless of other nutrient deficiencies (Rizzoli et al, 2006[30]; Holick, 2007[20]; Han et al, 2018[17]). In observational studies, optimal serum 25(OH)D levels have been significantly associated with improved musculoskeletal function and muscle strength (Bischoff-Ferrari et al, 2004[6]; Visser et al, 2003[36]).…”
Section: Introductionmentioning
confidence: 99%
“…Han et al also found that on post-menopausal women the mean serum vitamin D3 levels were significantly lower in patients with primary BPPV than controls (19.1 ± 5.2 versus 22.5 ± 5.8, P value < 0.001). 17 Sen et al reported that mean serum vitamin D3 levels in patients with BPPV and healthy controls were 20.3 ± 12.2 and 18 ± 10.1 ng/mL, respectively. The prevalence of vitamin D3 deficiency among the BPPV patients and controls was 76% and 42%, respectively.…”
Section: Discussionmentioning
confidence: 99%